Mechanical Study on the Marine Sediments of Bethioua Port to Valorizing them in the Manufacture of Bricks - Benyerou, D.; Boudjenane, N.; Belhadri, M. (Algerian Journal of Research and Technology (AJRT), 2019)
The work focuses on the practical use of sediments of Bethioua port in the manufacture of bricks. The sediments were introduced into the reference mixture with a substitution rate of 20% as a replacement for the clay used for making the bricks. The mix used in the Brickyard (reference brick) consists of 75% clay and 25% sand. The manufacture of reference brick test pieces and cylindrical-shaped marine sediment bricks was prepared from mixtures of clay, sand and a sediment substitution rate of up to 20% without any change in manufacturing process. The brick test pieces were fired at temperatures between 600 and 900 ° C with a cooking time of 6 hours and 24 hours. The brick test pieces produced were then subjected to compressive strength tests. The results obtained showed that the mechanical properties of the sediment-based brick with a substitution of 5 and 10% give a better resistance than the reference brick. The sediment substitution with this concentration by sediment increases the compressive strength with low temperature and low cooking time. The results of this study demonstrate that the production of bricks fired with the marine sediments of the Bethioua port improves significantly and gives a better resistance than the resistance of the reference brick for an addition of 5 and 10%. The rate of 15% gives a resistance comparable to that of the resistance of the slip of brick.